Turn Down the Heat : Confronting the New Climate Normal - World Bank Group (Washington, DC: World Bank, 2014)
This report focuses on the risks of climate change to development in Latin America and the Caribbean, the Middle East and North Africa, and parts of Europe and Central Asia. Building on earlier Turn Down the Heat reports, this new scientific analysis examines the likely impacts of present day (0.8°C), 2°C and 4°C warming above pre-industrial temperatures on agricultural production, water resources, ecosystem services, and coastal vulnerability for affected populations.